SAE Technical Paper Series 2001
DOI: 10.4271/2001-01-3606
|View full text |Cite
|
Sign up to set email alerts
|

Dilution Effects on the Controlled Auto-Ignition (CAI) Combustion of Hydrocarbon and Alcohol Fuels

Abstract: This paper presents results from an experimental programme researching the in-cylinder conditions necessary to obtain homogenous CAI (or HCCI) combustion in a 4-stroke engine. The fuels under investigation include three blends of Unleaded Gasoline, a 95 RON Primary Reference Fuel, Methanol, and Ethanol. This work concentrates on establishing the CAI operating range with regard to Air/Fuel ratio and Exhaust Gas Re-circulation and their effect on the ignition timing, combustion rate and variability, Indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 18 publications
0
45
1
Order By: Relevance
“…In the previous study, Christensn et al [6] compared ethanol with gasoline in a high compression ratio HCCI engine and demonstrated the high load limit that could be achieved with ethanol. Oakely et al [7] have shown that methanol and ethanol could be operated in CAI combustion mode over a wider range of relative air/fuel ratios and EGR concentrations than gasoline in a single cylinder engine with elevated intake charge temperature. Iida [8] conducted experimental studies of CAI combustion in a two-stroke ATAC engine and found that methanol provided larger range of CAI combustion than gasoline.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, Christensn et al [6] compared ethanol with gasoline in a high compression ratio HCCI engine and demonstrated the high load limit that could be achieved with ethanol. Oakely et al [7] have shown that methanol and ethanol could be operated in CAI combustion mode over a wider range of relative air/fuel ratios and EGR concentrations than gasoline in a single cylinder engine with elevated intake charge temperature. Iida [8] conducted experimental studies of CAI combustion in a two-stroke ATAC engine and found that methanol provided larger range of CAI combustion than gasoline.…”
Section: Introductionmentioning
confidence: 99%
“…Oakley et al [9,10] extended the investigation by performing detailed analysis of the heat release characteristics of the CAI combustion process in a 4-stroke gasoline engine. They found that the conventional Octane number is inadequate to describe the autoignition behaviour of fuels in a CAI engine.…”
Section: Introductionmentioning
confidence: 99%
“…Higher compression ratio will assist fuel to autoignite, but it leads to knocking combustion at higher load conditions, limiting the maximum power output of the engine. Some fuels, such as alcohol fuels [10], have shown to be superior to others, but a dual fuelled engine requires additional fuelling systems and adds more complexity to engine control, making them unsuited for automotive applications.…”
Section: Introductionmentioning
confidence: 99%
“…Methanol has been chosen as fuel because of the resulting feasible computational effort. Additionally, it should be mentioned that methanol is of interest as an alternative fuel [30,31].…”
Section: Introductionmentioning
confidence: 99%